Acute Lethal Pancreatitis.: Therapeutic Considerations - Torterolo, Edgardo; Viñuela, Enrique; Bergalli, Luis; Perrier, José Pedro; Sarroca, Carlos; Piñeyro, Alberto; Klempert, Haydée; Rinaldi, Bruno (Cirugía del Uruguay, 1981)
The medica! records of 22 patients with acute necrotic haemorrhagic pancreatitis are analyzed retrospectively, considering ciinical, pathological and therapeutic aspects.